Cell-in-cell phenomenon associates with aggressive characteristics and cancer-related mortality in early oral tongue cancer - Almangush, Alhadi (BMC Cancer, 2020)
BACKGROUND: Cell-in-cell structures (caused by cell cannibalistic activity) have been related to prognosis of many cancers. This is the first multi-institutional study to assess the prognostic impact of cell-in-cell structures in a large cohort of early oral tongue squamous cell carcinomas (OTSCC). METHODS: A total of 308 cases from five Finnish University Hospitals and from the A.C. Camargo Cancer Center, São Paulo, Brazil, were included in this study. Cell-in-cell structures were evaluated on surgical postoperative sections that stained with hematoxylin and eosin staining. RESULTS: We found that cell-in-cell structures associated with cancer-related mortality in univariable analysis with a hazard ratio (HR) of 2.99 (95%CI 1.52–5.88; P = 0.001). This association was confirmed in multivariable analysis (HR 2.22, 95%CI 1.12–4.44; P = 0.024). In addition, statistically significant associations were observed between the cell-in-cell structures and other adverse histopathologic characteristics including deep invasion (P <  0.001), high index of tumor budding (P = 0.007), worst pattern of invasion (P <  0.001), perineural invasion (P = 0.01), and stroma-rich pattern (P = 0.001). CONCLUSIONS: Our findings demonstrate a significant relationship between cell-in-cell formation and aggressive characteristics of early OTSCC. Cell-in-cell structures have a distinct impact as a novel prognostic indicator in early OTSCC and they can be easily assessed during routine pathology practice.